Naming Game Models, Simulations and Analysis - Chen, Guanrong; Lou, Yang.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a gradual introduction to the naming game, starting from the minimal naming game, where the agents have infinite memories (Chapter 2), before moving on to various new and advanced settings: the naming game with agents possessing finite-sized memories (Chapter 3); the naming game with group discussions (Chapter 4); the naming game with learning errors in communications (Chapter 5) ; the naming game on multi-community networks (Chapter 6) ; the naming game with multiple words or sentences (Chapter 7) ; and the naming game with multiple languages (Chapter 8). Presenting the authors' own research findings and developments, the book provides a solid foundation for future advances. This self-study resource is intended for researchers, practitioners, graduate and undergraduate students in the fields of computer science, network science, linguistics, data engineering, statistical physics, social science and applied mathematics. .
Introduction -- Preliminaries -- Finite-Memory Naming Game -- Naming Game with Multi-Hearers or Group Discussions -- Communications with Learning Errors. .
Keywords: Computational intelligence; Computational linguistics; Artificial intelligence; Computational Intelligence; Computational Linguistics; Artificial Intelligence